A binding cooperativity switch driven by synergistic structural swelling of an osmo-regulatory protein pair - Abhishek Narayan (Nature Portfolio, 2019)
The bacterial protein Cnu together with the transcription repressor H-NS regulate expression of virulence factors in an osmo-sensitive manner. Here authors show that the structure of Cnu swells with decreasing ionic strength driving the oligomerization of H-NS and regulating osmo-sensory response.